Mineralogy of selected soils from Guam - Carroll, Dorothy, 1907-1970 (Professional paper (Geological Survey (U.S.)), 1963)
"A mineralogical study of selected soil samples of Guam, including data on chemical composition, grain-size distribution, and comparison with other areas, as well as a description of soil profiles."